READING THE URBAN PLANNING IN INDONESIA: A JOURNEY TOWARDS SUSTAINABLE DEVELOPMENT - Setiawan, Wisnu (Universitas Muhammadiyah Surakarta, 2014)
Background: As urban population increases rapidly, urban environment has become a focus area in global agenda. Global agenda for this response has lead to the significance of sustainable development. The UN has also published several guidance on how to achieve sustainable environment. This agenda has been adopted across the world. However, such attitude appears to be problematic in the context of developing countries, including Indonesia particularly in the relationship with urban planning practice. Methods: This paper attempts to provide preliminary discussion of how urban planning practice in Indonesia has transformed to embrace the issue of sustainable development. It explores some readings relevant to the planning practice in contemporary context, from the postcolonial period until the recent reformation movement, using chronological interpretative approach on some available literatures on urban planning and development. Findings: The paper hints that the planning practice in Indonesia finds some challenges in adopting the idea of sustainable development, particularly from social sustainability point of view.